Entre Benjamín y Schmitt: el rompecabezas de José Aricó para pensar América Latina - Cortés, Martín (Nómadas. Critical Journal of Social and Juridical Science, 2011)
This text takes part of a PhD thesis -in progress- about the work of argentinean thinker José Aricó (1931-1991), focusing on his contributions to the production of a latin american marxism. In this case, we present a reading of some of the various sources that Aricó took in his attempts to enrich the Latin American critical thought. Showing versatility for that goal, our author went to various theoretical and political traditions (which may even be considered antagonistic to each other) with the main goal of "translating" them to the needs of thinking, from a Marxist perspective, the latin american specificity. His readings of Walter Benjamin, and the publication, in 1984, of The Concept of the Political, of Carl Schmitt, are two particularly important stages on Aricó´s path in regard to impact on latin american debates. Our hypothesis is that the originality and unorthodoxy of Aricó´s Latin American marxism lies in his ability to cmbine different traditions, with the common perspective of challenge marxism with various and different political and cultural currents and schools of thought.